1963
DOI: 10.1002/app.1963.070070520
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of experimental cis‐1,4‐polyisoprene latices

Abstract: Experimental latices of synthetic cis‐1,4‐polyisoprene and films and cellular objects produced from them are described. The latices of the synthetic polymers with molecular weights of about 2,000,000 are stabilized by anionic surfactants and have weight median particle diameters of about 0.9 μ and log normal particle size distribution. Tensile properties and flow characteristics of unvulcanized latex films could be regulated by introduction of controlled, small, amounts of crosslinking into the latex. Procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Presis et al have reported that excessive cross‐linking in the latex during maturation was shown to cause a loss of tensile strength in cured products. That was identified as the coalescence of latex particles during gelation which tend to get adversely affected by over curing . Manroshan and Baharin have explained the findings on tensile properties of nanosized CaCO 3 filled NR latex films supporting the hypothesis suggested by Presis et al The reduced tensile strength at higher loading of filler is attributed to filler‐filler interaction which goes beyond the enhanced filler–rubber interactions .…”
Section: Resultsmentioning
confidence: 57%
“…Presis et al have reported that excessive cross‐linking in the latex during maturation was shown to cause a loss of tensile strength in cured products. That was identified as the coalescence of latex particles during gelation which tend to get adversely affected by over curing . Manroshan and Baharin have explained the findings on tensile properties of nanosized CaCO 3 filled NR latex films supporting the hypothesis suggested by Presis et al The reduced tensile strength at higher loading of filler is attributed to filler‐filler interaction which goes beyond the enhanced filler–rubber interactions .…”
Section: Resultsmentioning
confidence: 57%
“…It has been explained elsewhere that these sharp decreases indicate the loading at which the filler bears more of the stress, and in some way it also indicates the limiting levels of loading [13,27]. Preiss et al [28] while explaining the decrease in strength of an experimental cis-1,4 isoprene with increase in filler loading even as the crosslink density had increased, adduced it to the increasing inability of the rubber latex particles to coalesce and cooperate fully with increasing crosslink; other workers also gave the same explanation [29].…”
Section: Swelling Resultsmentioning
confidence: 96%
“…At 30 phr of filler loading, the tensile strength decreased but the crosslink density (in reference to swelling index), M 100 , and M 300 showed an increase, as seen in Figures 2, 3, and 4, respectively. In their study on the characteristics of experimental cis ‐1,4 polyisoprene latices, Preiss et al10 reported that the decrease in tensile properties with increasing crosslink density is a consequence of the decreasing ability of the latex particles to coalesce and integrate fully as the concentration of crosslinks in the particles increases. In this study, the decrease in tensile properties at 30 phr of filler loading is attributed to an increase of filler to filler interaction compared to the filler to rubber interaction, which is needed to reinforce the rubber network.…”
Section: Resultsmentioning
confidence: 99%